Electrochemical hydrogenation of enones using a proton-exchange membrane reactor: selectivity and utility - Mitsudo, Koichi; Inoue, Haruka; Niki, Yuta; Sato, Eisuke; Suga, Seiji (Beilstein Journal of Organic Chemistry, 2022)
Electrochemical hydrogenation of enones using a proton-exchange membrane reactor is described. The reduction of enones proceeded smoothly under mild conditions to afford ketones or alcohols. The reaction occurred chemoselectively with the use of different cathode catalysts (Pd/C or Ir/C).
Keywords: enone; hydrogenation; iridium; palladium; PEM reactor

Partial reduction of enones, styrenes, and related systems - Baba, A.; Yasuda, M.; Nishimoto, Y. (Partial Reduction of Enones, Styrenes, and Related Systems, 2014)

(untitled) - Hicks, M. T.; Fedkiw, P. S. (J. Electrochem. Soc., 1998)

(untitled) - Pintauro, P. N.; Gil, M. P.; Warner, K.; List, G.; Neff, W. (Ind. Eng. Chem. Res., 2005)

(untitled) - Sedighi, S.; Gardner, C. L. (Electrochim. Acta, 2010)

(untitled) - Zhang, R.; Weidner, J. W. (ECS Trans., 2010)

(untitled) - Fonocho, R.; Gardner, C. L.; Ternan, M. (Electrochim. Acta, 2012)

(untitled) - Green, S. K.; Tompsett, G. A.; Kim, H. J.; Kim, W. B.; Huber, G. W. (ChemSusChem, 2012)

(untitled) - Ehteshami, S. M. M.; Zhou, W. J.; Chan, S. H. (Int. J. Hydrogen Energy, 2013)

(untitled) - Stuve, E. M.; Spies, K. A. (ECS Trans., 2013)

(untitled) - Stuve, E. M.; Spies, K. (ECS Trans., 2013)

(untitled) - Ehteshami, S. M. M.; Vignesh, S.; Rasheed, R. K. A.; Chan, S. H. (Appl. Energy, 2016)

(untitled) - Ogihara, H.; Maezuru, T.; Ogishima, Y.; Yamanaka, I. (ChemistrySelect, 2016)

(untitled) - Ogihara, H.; Maezuru, T.; Ogishima, Y.; Yamanaka, I. (Electrocatalysis, 2018)

(untitled) - Caravaca, A.; Garcia-Lorefice, W. E.; Gil, S.; de Lucas-Consuegra, A.; Vernoux, P. (Electrochem. Commun., 2019)

(untitled) - Carl, S.; Waldrop, K.; Pintauro, P.; Thompson, L. T.; Tarpeh, W. A. (ChemElectroChem, 2019)

(untitled) - Sato, M.; Ogihara, H.; Yamanaka, I. (ISIJ Int., 2019)

(untitled) - Takano, K.; Tateno, H.; Matsumura, Y.; Fukazawa, A.; Kashiwagi, T.; Nakabayashi, K.; Nagasawa, K.; Mitsushima, S.; Atobe, M. (Chem. Lett., 2016)

(untitled) - Takano, K.; Tateno, H.; Matsumura, Y.; Fukazawa, A.; Kashiwagi, T.; Nakabayashi, K.; Nagasawa, K.; Mitsushima, S.; Atobe, M. (Bull. Chem. Soc. Jpn., 2016)

(untitled) - Fukazawa, A.; Takano, K.; Matsumura, Y.; Nagasawa, K.; Mitsushima, S.; Atobe, M. (Bull. Chem. Soc. Jpn., 2018)

(untitled) - Egbert, J. D.; Thomsen, E. C.; O’Neill-Slawecki, S. A.; Mans, D. M.; Leitch, D. C.; Edwards, L. J.; Wade, C. E.; Weber, R. S. (Org. Process Res. Dev., 2019)

(untitled) - Liu, J.; Chen, R.; Zhu, X.; Liao, Q.; Ye, D.; Zhang, B.; Liu, M.; Chen, G.; Wang, K. (RSC Adv., 2019)

(untitled) - Fukazawa, A.; Minoshima, J.; Tanaka, K.; Hashimoto, Y.; Kobori, Y.; Sato, Y.; Atobe, M. (ACS Sustainable Chem. Eng., 2019)

(untitled) - Nogami, S.; Nagasawa, K.; Fukazawa, A.; Tanaka, K.; Mitsushima, S.; Atobe, M. (J. Electrochem. Soc., 2020)

(untitled) - Nogami, S.; Shida, N.; Iguchi, S.; Nagasawa, K.; Inoue, H.; Yamanaka, I.; Mitsushima, S.; Atobe, M. (ACS Catal., 2022)

(untitled) - Fukazawa, A.; Tanaka, K.; Hashimoto, Y.; Sato, Y.; Atobe, M. (Electrochem. Commun., 2020)

(untitled) - Fukazawa, A.; Shimizu, Y.; Shida, N.; Atobe, M. (Org. Biomol. Chem., 2021)

(untitled) - Yoshida, J.-i.; Suga, S.; Suzuki, S.; Kinomura, N.; Yamamoto, A.; Fujiwara, K. (J. Am. Chem. Soc., 1999)

(untitled) - Suga, S.; Suzuki, S.; Yamamoto, A.; Yoshida, J.-i. (J. Am. Chem. Soc., 2000)

(untitled) - Mitsudo, K.; Yamamoto, J.; Akagi, T.; Yamashita, A.; Haisa, M.; Yoshioka, K.; Mandai, H.; Ueoka, K.; Hempel, C.; Yoshida, J.-i.; Suga, S. (Beilstein J. Org. Chem., 2018)

(untitled) - Mitsudo, K.; Matsuo, R.; Yonezawa, T.; Inoue, H.; Mandai, H.; Suga, S. (Angew. Chem., Int. Ed., 2020)

(untitled) - Kurimoto, Y.; Yamashita, J.; Mitsudo, K.; Sato, E.; Suga, S. (Org. Lett., 2021)

(untitled) - Brieger, G.; Nestrick, T. J. (Chem. Rev., 1974)

(untitled) - Bagnell, L.; Strauss, C. R. (Chem. Commun., 1999)

(untitled) - Albrecht, M.; Crabtree, R. H.; Mata, J.; Peris, E. (Chem. Commun., 2002)

(untitled) - Hillier, A. C.; Lee, H. M.; Stevens, E. D.; Nolan, S. P. (Organometallics, 2001)